Mexican Banks’ Acceptance and Use of Twitter to Assist in Evaluating Farm Loan Applications: Exploring the Role of Agricultural Loans on Food Security - Robert Strong; Larry M. Dooley; Travis L. Irby; Lori Unruh Snyder (Journal of International Agricultural and Extension Education, 2014)
Food security issues are a global concern of countless citizens irrespective of professional vocation or individual residence. Literature indicated numerous factors affect food security and researchers should continue examining elements that may influence food insecurity. The lack of acquiring finance can prohibit farmers from planting and harvesting crops, and thus, is a cause of food insecurity. Mexican banks receive economic agricultural forecasts from the Ministry of Agriculture. This study sought to describe Mexican banks’ degree of acceptance and use of the Ministry’s information on Twitter. Fourteen (N = 14) agricultural loan administrators from Mexican banks were examined to address this study’s research objectives. Agricultural loan administrators were interviewed to determine their acceptance and use of the Ministry’s statistics on Twitter. Participants reported the dissemination of agricultural statistics on Twitter saved banks time by providing a source that delivered specific crop forecasts and not all crop outlooks simultaneously. Twitter can be used to let a bank know the particular value of a commodity in real time thus being able to inform not only their financial decisions but notify farmers pursuing loans. The Ministry of Agriculture’s Twitter feeds increased performance and communication while requiring little effort due to the pervasive nature of the technology. The use of information disseminated on Twitter allowed farmers to receive funds faster thus enabling them to plant and harvest crops in order to aid in the battle against food insecurity.
Keywords: Food Security; Agricultural Loans; Twitter; UTAUT; Banks; Ministries of Agriculture